Sociolinguistics Study of Swear Words Found in Songs from Album â€œThe Sailorâ€ 2019 by Rich Brian - Wiguna, I Made Candra; Laba, I Nengah; Dewi, Ni Luh Desy Suari (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2024)
This research examines the use of swear words found in the lyrics of songs from album â€œThe Sailorâ€ 2019 by Rich Brian. It employs qualitative analysis to categorize and explore swear words, using frameworks by Wardhaugh (2006) for classification and Rothwell (1973) for purposes. Seven profanity categories are identified as mother in-law, animal, sex, death, excretion, bodily function, and religious matters. The study uncovers five purposes for profanity use in the songs: to get attention, to discredit someone or something, to provoke, to create interpersonal identification, to provide catharsis. Analyzing 89 instances, 11 profanity types are found, with "fuck" being most frequent (35 times). The prevalent purpose is to â€œprovide catharsis.â€ Swear wordsâ€™ presence underscores its societal significance, revealing diverse meanings based on users and contexts. This research illuminates sociolinguistic aspects of rap songs and swear wordsâ€™ role in today's society.